Software process models vs descriptions: What do practitioners use and need?. Issue 11 (6th June 2017) - Diebold, P.; Scherr, S.A.
Abstract: It is commonly known that software or system development processes are very important for getting a high‐quality product. Such processes can be described in many different ways, from textual documents to existing modeling notations. Before dealing with the overall goal of improving the description of development processes, this paper evaluates the current state of practice regarding process descriptions and reasons for that. A major focus is on the degree of formality. Based on an interview guideline, a series of 12 interviews was conducted in German companies of different sizes. The results were analyzed to come up with the current usage of and need for software process models or descriptions. In general, our results confirm the literature statement that in industrial practice the majority of processes descriptions are detailed but rather focus on informal descriptions than formal notations or models. Nevertheless, they use semiformal process descriptions containing different graphical, table‐based, or structured‐text elements for representation. It is interesting that even if companies do not want to use formal models; they would like to have their advantages and even often have the detailed information necessary for formal models. Overall, our findings provide evidence on the state of practice regarding usage of process descriptions and models and show the need for future work in this area.